Statistical Modelling of Drying Characteristics of Unripe Plantain (Musa Paradisiaca) Slices - Ekeke I C; Nkwocha A C; Kamen F L; Nwabuchiri P; Agbo J C (International Journal of Engineering and Management Research, 2019)
This work is designed to carry out the statistical modelling of the drying characteristics of unripe plantain (Musa paradisiaca) slices and to study the effect of drying temperature and slice thickness on drying characteristics. The test samples were dried in a laboratory scale oven dryer at varying temperatures of 700C, 800C and 900C, and different slice thicknesses of 2mm, 3mm and 4mm.The result obtained indicated that drying temperature and slice thickness had significant effect on drying rate and hence moisture profile. The moisture ratio – drying time data obtained were fitted to ten thin layer drying models. The fit quality obtained with each model was evaluated using statistical tests namely; coefficient of determination (R2), root mean square error (RMSE), reduced chi-square (X2), and standard error of estimate (SEE). Although most of the models fitted quite well to the experimental data, Page and Modified Page models showed the highest average R2 and the lowest average RMSE, X2 and SEE values. Page and modified Page models were selected and found suitable to represent the drying characteristics of unripe plantain slices and predict drying times.